An assessment of using sukuk for waqf property development in India - Jasir Mohtesham, Mohammed Meeran; Syed Azman, Syed Marwan Mujahid; Hai, Abdul; Shahid, Mohd (IIUM Press, 2021)
The purpose of this study is to assess the viability of using Sukuk as a tool for financing the development of waqf properties in India. Using different reports, literature, and considering Indian Waqf Act, this study introduces Sukuk for waqf property development in India. Critical analysis of case studies of successfully employed waqf property development in Saudi Arabia and Singapore is also undertaken. From the various literature and reports, this paper finds that there is a huge economic potential for Indian waqf properties. However, due to several issues, one of them being a financial issue, waqf in Indian is unable to achieve its potential. Furthermore, the study also finds that there is a possibility to introduce Mudharabah Sukuk for this purpose. As Indian Waqf Act prohibits the sale, gift, or transfer of the waqf properties, Mudharabah can be the best suitable tool for financing the development of waqf properties. This study is conceptual in nature. Further studies can consider empirical research that considers factors such as awareness, knowledge, perception, and readiness to invest in Sukuk. The findings from this paper can be used to introduce Sukuk for waqf property development in India. The successful implementation will lead to the revitalisation of waqf properties in the country which will eventually result in the upliftment of Muslim society from social and educational backwardness and benefit them at-large. This paper also provides information about the potential of Indian waqf properties which very essential for the investors in Sukuk. This study is the first one to talk about the Sukuk for waqf property development in India.